Development of Interactive Media in Learning to Read and Write Javanese Script: Literature Review - Wahyuni, Mita (Abjad Journal of Humanities & Education, 2023)
Learning to read and write Javanese script is a skill that students must master from elementary school to high school/equivalent in Javanese language lessons. In reality, there are several problems in this learning, including (1) teachers' difficulties in teaching Javanese script, (2) students having difficulty understanding Javanese script material, and (3) students feeling bored because of the minimal use of Javanese script learning media. Media is a means to make it easier for students to understand the material. The forms of media used can be varied, such as interactive media. The research method used is a Systematic Literature Review (SLR), which identifies, reviews, evaluates, and interprets all available research. Based on the research results, 17 articles on the development of interactive media in learning to read and write Javanese script were found in the Google Scholar database with the help of the Publish or Perish application. The media that has been developed is intended for elementary, middle and high school students and even the general public. Interactive media is developed using the latest technology, such as Adobe Flash software, Macromedia Flash, RPG Maker MV, and Augmented Reality (AR) applications. With these facilities, researchers use various research methods, including ADDIE, Research and Development (R&D), Virtual Machine Forensic Analysis and Recovery (VMFAR), Waterfall, Lee & Owens, Multimedia Development Life Cycle (MDLC), and others. Based on the test results, it can be seen that interactive media has various benefits, such as students becoming more active and independent in learning, the quality of student learning, making it easier for teachers to explain the material, making it easier for students to understand the material, and not being easily damaged.